Community case study: Community-driven strategies to build a socially inclusive rural county - Ablah, Elizabeth; Long, Nadine; Pacheco, Christina M.; Sutter, Maddi; Bohnert, Shelby; Wolff, Sharon Fitzgerald; Finocchario-Kessler, Sarah (Frontiers in Public Health, 2025)
Mitchell County, Kansas is a rural county with a strong sense of local identity and a population committed to community well-being. Like many rural areas, however, residents experience structural challenges to social connection, including geographic isolation, demographic shifts, and limited access to inclusive services. These issues were further exacerbated by the COVID-19 pandemic. Through a federally funded initiative, Communities Organizing to Promote Equity (COPE), Mitchell County stakeholders developed community-driven strategies to address social isolation, with special consideration on how to include new immigrant residents. This case study outlines the intervention, centered on engagement and trust-building, cultural inclusion, employment access, and wrap-around supports; highlighting how other rural communities might replicate this work to build more welcoming, connected, and inclusive environments.